1999
DOI: 10.1038/sj.sc.3100780
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Lipo prostaglandin E1 on cauda equina blood flow in patients with lumbar spinal canal stenosis: myeloscopic observation

Abstract: Study Design: Myeloscopic examination was performed to observe the cauda equina in patients with lumbar spinal canal stenosis before and after treatment with Lipo prostaglandin E1, a strong peripheral vasodilator. Objectives: The purpose of this study was to clarify the e ects of Lipo prostaglandin E1 on blood¯ow in the cauda equina in patients with lumbar spinal canal stenosis. Setting: Japan, Kagoshima Methods: We performed myeloscopic observations of morphological changes in blood vessels running along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Since it can be assumed that the impaired intraradicular blood flow is improved by the drug in patients whose NIC responds to administration of PGE1, this agent can be used for screening and staging of the disease. Yone et al [82] have reported that when lipo-PGE1 was injected intravenously in 11 LCS patients during surgery, symptoms were alleviated in 6 patients with dilation of vessels running along the cauda equina, but not in 5 patients with no change of their vessels. Dezawa et al [83] observed the movement of red blood increased intraradicular blood flow in the normal nerve root without compression, but the increase of blood flow observed in the compressed region of the nerve root exhibiting Wallerian degeneration was transient and not sustained (Figures 10 and 11).…”
mentioning
confidence: 99%
“…Since it can be assumed that the impaired intraradicular blood flow is improved by the drug in patients whose NIC responds to administration of PGE1, this agent can be used for screening and staging of the disease. Yone et al [82] have reported that when lipo-PGE1 was injected intravenously in 11 LCS patients during surgery, symptoms were alleviated in 6 patients with dilation of vessels running along the cauda equina, but not in 5 patients with no change of their vessels. Dezawa et al [83] observed the movement of red blood increased intraradicular blood flow in the normal nerve root without compression, but the increase of blood flow observed in the compressed region of the nerve root exhibiting Wallerian degeneration was transient and not sustained (Figures 10 and 11).…”
mentioning
confidence: 99%
“…Thus, compared with PTH, which cannot be administered orally due to its peptide nature, EP4A may be superior in terms of possible clinical oral use in the patients. Several forms of PG drugs have already been used in the clinical setting such as those to increase circulation in the case of obstructive arteritis (Makita et al 1997) or lumbar canal stenosis (Yone et al 1999). Together, these observations suggest that orally administrated EP4A may be safe and effective in combination with inhibition of OPN action.…”
Section: Discussionmentioning
confidence: 66%
“…Several authors have reported that PGE1 also enhanced blood ow in the cauda equina. 22,23 Upon consideration of these facts, we believe that PGE1 may be e ective in simultaneously reducing hypertension and restoring spinal blood¯ow.…”
Section: Discussionmentioning
confidence: 99%